From the microbial to the mechanical : environmental impacts on coral nitrogen cycling, microbial communities, and skeletal properties - Moynihan, Molly Anne (Nanyang Technological University, 2021)
Corals are architects of their own environment that build critical structure, recycle nutrients, host microorganisms, support biodiversity, and provide storm protection to coastal populations. However, despite the importance of corals' skeletal structure and their predicted vulnerability to future climate change, few studies have examined the mechanical and crystallographic properties of coral skeletons at the micro- and nano-scales. Additionally, the coral skeleton harbours a diverse microbial community, whose role in coral physiology and reef nutrient cycling is currently unknown. This work takes an integrative and interdisciplinary approach to coral science and aims to address several key questions surrounding both the structural properties of coral skeletons, as well as nutrient cycling within the coral tissue and skeleton. Using Porites cores from across Asia (Thailand, Singapore, Taiwan), skeletal hardness, stiffness (Young's modulus), and micro-fracture stress were measured to investigate how skeletal properties change locally and regionally over time. Select micro-mechanical measurements were paired with high resolution mapping of aragonite crystal orientation to further connect mechanical properties with the physical process of coral calcification. Large and unexpected variability in material properties and mechanical anisotropy were found. As Porites corals are likely to incur higher forces in the direction parallel to corallite growth, particularly from predation, anisotropy may provide the skeleton with a structural advantage. Comparison of mechanical data with skeletal geochemistry and organic content reveals that changes to the organic matrix content and/or Sr substitution in the aragonite lattice could drive changes in skeletal stiffness, hardness, and embrittlement. Between coral samples, environments with higher SST, lower salinity, and increased sedimentation exhibit lower absolute mechanical properties. Organic content and Ba/Ca ratios suggest that increasing runoff, sedimentation, or feeding could increase a skeleton's susceptibility to incur irreversible damage via cumulative micro-fracture events. Within individual coral cores, skeletons had increased stiffness and hardness when stress was applied parallel to the primary growth direction. While massive Porites skeletons can withstand wave forces well beyond average storm surges, in building a stiff skeleton, corals contribute high quality material to reef substrate and decrease the rate of bioerosion by predators and borers. If the coral is significantly embrittled, as observed in cores from Singapore, faster erosion is expected, resulting in a decrease in the quality of reef substrate and an increase in colony dislodgement. To build their skeletons and thrive in nutrient-poor environments, corals rely on efficient recycling of nitrogen and carbon between the host and their symbiotic dinoflagellate algae. However, other coral-associated microbes may also play a key role in holobiont functioning and reef biogeochemistry. Nitrogen-fixing bacteria and archaea, known as diazotrophs, are common members of the coral microbiome, and significant rates of nitrogen fixation can occur within the coral tissue and mucus. However, few aquarium-based studies have been conducted, and existing experimental results vary greatly in the magnitude and fate of fixed nitrogen. To address these gaps, a two-year time series of in-situ experiments using isotopic labelling techniques was conducted to quantify the rates of fixed nitrogen assimilation in the coral host and symbiont tissue, skeletal endolithic community, and coral mucus. Due to its monsoonal climate, nutrient concentrations on Singapore's reefs range from nutrient-rich to nutrient-poor throughout the year, providing a natural set of experimental conditions to investigate the range and variability of coral-associated nitrogen fixation. Incubation results suggest low nitrogen fixation rates associated with coral host and symbiont tissue (1-3 ng N cm-2 h-1), and that 5-10 ng N day-1 cm-2 of coral-associated fixed nitrogen are transferred to the water column via mucus. Skeletal analysis shows that coral endolithic microbial communities could fix up to 10 ng N cm-2 h-1 and are a significantly overlooked source of diazotroph-derived nitrogen to the coral holobiont. From an experiment performed during nutrient-replete conditions, multi-marker metabarcoding (nifH, 16S and 18S rRNA) of DNA- and RNA-based communities was used to characterize the microbial communities of the coral tissue and endolithic layer. Analysis of the DNA- and RNA- based microbial communities shows greater relative diazotrophic activity in the skeleton, and that the most abundant putative diazotrophs in the total community are unlikely to be responsible for the majority of nitrogen fixation. As nitrogen fixation is a source of new nitrogen into the ecosystem, constraining rates and identifying the key taxa involved in this process is not only of significance for our understanding of the functional role of coral-associated microbes, but also for larger scale biogeochemical modeling of tropical reef environments.